RETRACTED: DEAD-Box Helicase 5 Interacts With Transcription Factor 12 and Promotes the Progression of Osteosarcoma by Stimulating Cell Cycle Progression - Chen, Yanchun; Wang, Qiaozhen; Wang, Qing; Liu, Jinmeng; Jiang, Xin; Zhang, Yawen; Liu, Yongxin; Zhou, Fenghua; Liu, Huancai (Frontiers in Pharmacology, 2019)
Osteosarcoma (OS) is a common malignant primary bone tumor. Its mechanism of development and progression is poorly understood. Currently, there is no effective therapeutic regimens available for the treatment of OS. DEAD-box helicase 5 (DDX5) is involved in oncogenic processes. This study aimed to explore the role of DDX5 in the development and progression of OS and its relationship with transcription factor 12 (TCF12), which is as an important molecule of Wnt signaling pathway. We found that the expressions of DDX5 and TCF12 protein were significantly higher in OS patients tissues and in the MG63 cells than in the corresponding normal tissues and human osteoblast cell hFOB 1.19. Overexpressions of both DDX5 and TCF12 were associated with clinicopathological features and poor prognosis of OS patients. siRNA based knockdown of DDX5 inhibited the proliferation of MG63 cells as demonstrated by an in vitro MTS assay and 5-ethynyl-2-deoxyuridine DNA proliferation detection, and promoted apoptosis of MG63 cells measured by flow cytometry. In addition, DDX5 knockdown inhibited the MG63 cell migration and invasion on transwell assays. Further experiments showed that DDX5 knockdown not only inhibited the expression of TCF12 but also decreased the mRNA and protein levels of Cyclin E1, an important regulator of G1–S phase progression, suggesting that DDX5 was required for the entry of cells into S phase. Overexpression of TCF12 reversed the cell proliferation, migration and invasion in MG63 cells induced by DDX5 knockdown accompanied by the upregulation of Cyclin E1. Additionally, we observed that DDX5 interacted with TCF12 in both OS tissues and MG63 cells by Co-immunoprecipitation assays. Taken together, our study revealed that DDX5 interacts with TCF12 and promotes the progression of OS by stimulating cell cycle progression. Our results suggest that DDX5 and TCF12 could be potential biomarkers for the diagnosis and treatment of OS.